MONITORING GEOMETRY FOR HIGHWAY CONSTRUCTION USING UAV-PHOTOGRAMMETRY - Anzalta Minfadlika Failusuf - Nim: 15114095 , Nifa
Infrastructure development to improve connectivity and ease the mobility of people and stuff is road construction, toll road, and bridges. In accordance with the construction phase of the technical planning, monitoring the road construction is need to be done. In addition, with monitoring can be identified and anticipated problems in construction which may arise to take action as early as possible. Conventional terestris methods of monitoring construction of roads took data with high risk, spend the time and less effective. The unmanned aerial vehicle use in photogrammetry becomes an alternative solution in monitoring the road construction. This research aims to know the accuracy of unmanned photogrammetry technique from the camera with sensor size 6.25 x 4.68 mm and 23.5 x 15.6 mm in helping monitoring roads construction. Beside that, this research also aims to define the right data processing techniques to produce the precise information of horizontal and vertical geometric. Three technique processing that would be checked are orthophoto digitization, stereoplotting and stereomateplotting. Validation of the data is carried out by means of compare the results of plotting to data terrestrial and shop drawing. Best findings is unmanned photogrammetry technique can be used in monitoring geometry of road construction. The value of RMSE check from camera with sensor size 23.5 x 15.6 mm with the stereoplotting technique is the best technique compared with the other camera and methods of plotting, where the difference value are 5.8 cm (± 2 GSD, ground sampling distance) in horizontal axis and 7.5 cm (± 3 GSD) vertical axis. The RMSE value check are done in a various data processing scenario and case study that will be explained in this undergraduate thesis.